Improvement of Data Communication and Computer Networks Skills through Computer Network and Cyber Security Training at TCK Learning Center Hong Kong - Suci Resmiyati; Rachel Intania Rifany; Nyi Mas Mia Rahmawati; Vika Febri Mulyati; Fesa Asy Syifa Nurul Haq; Lukman Medriavin Silalahi; Chris Drake (An International Journal Tourism and Community Review, 2025)
Data communication and computer networking training at TCK Learning Centre Hong Kong is organized to address the need for increased technology literacy among Indonesian migrant workers in the face of digital globalization challenges. This activity is designed in a hybrid format (online and offline) with an approach that integrates theory and practical applications. The goal of this event is to enhance participants' understanding of basic networking concepts, technical skills in configuration and troubleshooting, as well as their analytical abilities in addressing data communication challenges. The implementation method includes material presentation, case studies, interactive discussions, and evaluation through questionnaires. The results of the activity show that the participants' understanding level is very good, with the majority stating that the material presented is easy to understand and of high quality. This activity is also in line with the targets of Sustainable Development Goals (SDG), namely quality education and decent work. This training not only empowers participants individually but also strengthens the image of TCK Learning Centre as a strategic partner in the development of a skilled ICT-based workforce.